CRACK INDIRECT IDENTIFICATION METHOD FOR DYNAMIC VIBRATION FREQUENCY OF WIND BLADES - WU QiQiang; GUO ShuaiPing; WANG Gang; LI XueJun (Jixie qiangdu)
In view of the problem of crack location in wind turbine blade, based on the relation between the difference ratio parameter of natural frequency of cracked blade and damage location, the crack location parameter of natural frequency difference ratio was put forward.The database of crack location parameters was established by numerical simulation calculation, the crack location parameters and crack location criteria were put forward to realize the crack location in the blade. Meanwhile, the variation law of crack location parameters in the crack zone was studied. The mapping relationship between the crack location parameters and the relative position of the crack region was established, and the accurate location of the blade crack interval was realized. The effectiveness of the method is verified by numerical simulation, and the positioning accuracy is high, which provides a powerful basis for practical application.